Effects of using white flour, zinc oxide and zinc ash as an admixture in mortar and concrete. (2022) - Anandaraj, S.; Karthik, S.; Vijaymohan, S.; Rampradheep, G.S.; Indhiradevi, P.; Anusha, G.
Abstract: This paper focuses on finding out both environment friendly and easily available admixture for concrete. Admixtures are property modifying compounds used in construction industry. They can be added both at production or during batching. Admixtures can be used to alter various properties of concrete namely compressive strength, workability, setting time, crack resistance, durability, permeability etc. Effect of an admixture usually vary with the characteristics of cement used and proportion in which it is mixed. Starch can be used as an admixture in concrete. In this study white flour, zinc oxide and zinc ash which consists of about 80 to 90% zinc oxide was used. various percentages of white flour were added in replacement with cement and was found that the setting time of concrete/ cement increases with the addition of starch admixtures. Compressive strength of concrete increases with the increase in percentage of white flour until 1%. Any further increase in in white flour causes decrease in strength of concrete. Thus, starch admixtures namely white flour can be used instead of chemical admixtures, thereby reducing the additional cost incurred while using chemical admixtures. Also zinc ash which consists mainly of zinc oxide is tested for its use as an admixture in concrete. zinc ash is a waste product of zinc manufacturing industry. By effectively using it in concrete both safe disposal of waste material and required admixture property in concrete could be achieved. It was found that addition of zinc oxide greatly increases the compressive strength of concrete about 20%.